Prostanoid receptors (version 2019.5) in the IUPHAR/BPS Guide to Pharmacology Database. (2019) - Breyer, Richard M.; Clapp, Lucie; Coleman, Robert A.; Giembycz, Mark; Heinemann, Akos; Hills, Rebecca; Jones, Robert L.; Narumiya, Shuh; Norel, Xavier; Pettipher, Roy; Sugimoto, Yukihiko; Uddin, Mohib; et al.
No abstract available